Tribological behaviors of in situ TiB2 ceramic reinforced TiAl-based composites under sea water environment. Issue 5 (1st April 2017) - Wang, Long; Cheng, Jun; Qiao, Zhuhui; Yang, Jun; Liu, Weimin
Abstract: In this paper, the tribological behaviors of 20 and 40 vol% in situ TiB2 reinforced TiAl-based composites sliding against SiC balls were investigated in artificial sea water, and TiAl alloy was also studied as a comparison. The results showed that the TiAl-TiB2 composites are lubricated in artificial sea water and TiB2 is effective to improve the wear resistance of the TiAl alloy. Also, it was found that the tribological behaviors have a dependency on the applied loads and sliding speeds. Worn surface morphologies and composition together with electrochemical behaviors of the materials were evaluated and related to the tribological behaviors.